Assessment of pollen and honey diet of Tetragonisca angustula fiebrigi Schwarz in the Chaco dry forest by using pollen analysis. Issue 4 (4th July 2021) - Vossler, Favio Gerardo
Abstract: Pollen and honey resources composing the diet of Tetragonisca angustula fiebrigi Schwarz were assessed using pollen analysis of wild colonies sampled in two kinds of native dry forests of the Chaco region. Different measurements: direct pollen count, relative volume, diversity and evenness indices, value of importance of species (SI), and index of relative importance (IRI) were compared. The IRI identified the most important pollen resources as Prosopis (IRI = 1619), Schinopsis type (IRI = 1578), Trithrinax schizophylla (IRI = 972) and Capparicordis / Sarcotoxicum (IRI = 587), and according to SI the honey resources were Schinopsis type (SI = 117.41), Maytenus type (SI = 101.89), Prosopis (SI = 86.47) and Ziziphus mistol (SI = 50.93). The absolute pollen analysis of honey revealed that all samples were rich in pollen grains. Floral resources were most homogeneously foraged during spring and summer when a high number of flowerings were available and the highest temperatures were recorded. These optimal conditions for bee foraging activity also allowed for the highest diversity indices in these seasons. However, heterogeneous foraging and low diversity were detected during winter and autumn. Most pollen and honey resources belonged to generalised small flowers of diverse plant lineages. The IRI was more comprehensive to identify the most important pollen resources than the commonly used direct pollen count, as it also includes relative volume and frequency of occurrence, and SI was the most thorough for studying the honey resources. This study provides helpful information for sustainable meliponiculture and forest conservation.